Essay on Saving and Consumption - Nikola Fabris; Jelena Galić (Journal of Central Banking Theory and Practice, 2015)
Consumption and saving decisions are at the heart of both short- and long-term macroeconomic analyses. Since the global crisis outbreak, one of the main issues for indebted countries has been whether to pursue a policy which promotes saving or to try to induce economic growth by increasing consumption. Consensus has not been reached on this issue, which is based on an old debate of whether a country should pursue a policy of Keynesianism or monetarism. Ergo, this essay discusses arguments supporting both approaches, primarily through theoretical arguments of Keynesianism and monetarism. The authors concluded that in a crisis environment, consumption policy should be given priority; however, a precondition for this is that a country was not overburdened prior to the crisis outbreak, i.e. a successful crisis management policy should, in fact, be pursued over the periods of expansion.
Keywords: E21; E00; 330; consumption; saving; Keynesianism; monetarism; crisis